Primierly Study of Kinematic Analysis and Potential Prospection of Geothermal Mountain Pandan with Ordinary Kriging Method - Arhananta, Arhananta (Departemen Teknik Geologi, 2018)
In Indonesia, Geothermal has 312 potential points, 67 work areas, with total electricity generated 28,910 MWe. This paper discusses the geothermal system in Pandan mountain Bojonegoro regency. The method used is the study of previous research and then conducted surface mapping on the area that is interpreted from google earth image, SRTM, then the subsurface data in the form of bouger anomaly data, and chemical analysis of hotspring manifestation. After that analyzed by ArcGIS and Surfer software to create prospect area through ordinary of kriging method. The prospect area is obtained through data fracture and fault density by ordinary kriging method located in hot springs. Regionally of Java island on the gravity anomaly map of the area around Pandan mountain shows a low gravity anomaly with east-west straightness that developed into West-southeast in the western part of Mount Pandan. Then from the interpretation of google earth imagery is also found direction of NW coherent with data withdrawal linement of image DEM SRTM. At the observation stage of the field in accordance with the interpretation of previous methods in which the hot springs controlled by fault field is lateral fault Banjar Times, Sambongrejo lateral fault, Kali Gandong lateral reverse faults, and lateral Bladogan fault which is smaller in scale caused by spine hoe. Geothermal manifestations in the form of hot springs Selogajah, Tadahan, Banyukuning and Jarikasinan into 6 geochemical data but in this analys just from 2 data (3 Banyukuning, 1 Selogajah) and Based on the results of plotting on the triangle Cl-, HCO3-, and SO42- as seen in hot water in the Selogajah and Banyukuning areas is located in Cl- which can be classified as a type of boiled water and HCO3 can be classified as peripheral water. Based on the results of plotting on the triangles K, Na-, and Mg- as shown in Figs, hot water in the Selogajah area is classified as partial equilibrium and Banyukuning can be classified as immature water Based on the results of plotting on triangles Li, Cl-, and B- as seen in Figs, hot water in Selogajah and Banyukuning areas is dominated by Cl. However, from data gochemistry indicating the outflow is not necessarily true because water passes through a reservoir that has carbonaceous properties, there is still a percentage if the water heating area is the upflow of the density of the structure which shows a high permeability. The potential electricity generated by Mount Pandan is 50 MWe from 1206.5 Mwe of East Java potential. Keywords: hot water geochemistry, image, structural geology, remote sensing, ordinary kriging